Structural, electronic and optical properties of defect chalcopyrite CdGa2S4 and HgGa2S4 compounds by first principles - Osman, Norhaslinda (2014)
The physical properties of defect chalcopyrite compounds are discussed here. Initial study are carried out under the framework of density functional theory by keeping in view the device manufacturing characteristics relating to structure, energy band configuration and bonding nature of the selected PbGa2S4 and HgGa2S4 defect chalcopyrite compounds. The computational work are executed using highly accurate full potential linearized-augmented plane wave + local orbital approach through the latest edition of Wien2k software. In a next step, the electronic properties of PbGa2S4 and HgGa2S4 defect chalcopyrite compounds are investigated. Precise band gap are calculated by employing GGA and LDA techniques. This work provided a comprehensive theoretical study of the physical properties with special emphasis on structural and electronic properties of defect chalcopyrite compounds.